PEMANFAATAN HASIL HUTAN BUKAN KAYU (HHBK) OLEH MASYARAKAT DESA LABUAN KUNGGUMA - Fifin, Fifin; Hamzari, Hamzari; Muthmainnah, Muthmainnah; Erniwati, Erniwati (Universitas Tadulako, 2021)
This research is a study of the utilization of non-timber forest products (NTFPs) by the villagers of Labuan Kungguma. In general, the community around the forest utilizes the existence of the forest to fulfill their daily needs and the income they get from most non-timber forest products (NTFPs). The research was carried out for three months from February to April 2019. The research location was located in Labuan Kungguma Village, Labuan District, Donggala Regency, Central Sulawesi. The purpose of this research was to examine Community Involvement in Non-Timber Forest Product Utilization (NTFP) and Constraints faced by the community in utilization (NTFP) in Labuan Kungguma Village, Labuan District Donggala Regency. Data collection techniques through observation, interviews using questionnaires, the analysis used is descriptive analysis by presenting data through tables and calculating percentages. The results showed a form of community involvement in the utilization of forest products (NTFPs), namely a form of collection of non-timber forest products (NTFPs) and a form of farmer group involvement. Community and farmer group involvement in the collection of forest products (NTFPs) is by taking it directly in the forest area. Types of forest products used by the community include rattan, bamboo and honey.Keywords : Utilization, Non-Timber Forest Products.